Evaluation of promising safflower accessions/breeding lines to aphid, Uroleucon compositae: Evaluation of promising safflower accessions/breeding lines to aphid, Uroleucon compositae - P SATYA SRINIVAS; N MUKTA; KADIRVEL PALCHAMY (Journal of Oilseeds Research, 2023)
Identification of stable resistant sources for aphids is essential for development of aphid resistant safflower cultivars. Among the different lines evaluated, a high oleic acid line, BC2-F6-38-9-4-OL was found consistently tolerant to aphid. Another nine accessions were confirmed moderately tolerant.